Using word study instruction with developmental college students. (7th October 2013) - Atkinson, Terry S.; Zhang, Guili; Phillips, Shannon F.; Zeller, Nancy
<x xml:space="preserve">Abstract</x> This study investigates the effect of word study instruction on the orthographic knowledge of college students enrolled in a developmental reading course. Results revealed significantly greater improvement in orthographic knowledge in students who received word study instruction when compared with those in a control group, suggesting that the word study approach was effective for these students. Because of the influence of orthographic knowledge on spelling, writing and reading, additional research is merited to examine how word study intervention impacts the reading behaviours and academic achievement of college students enrolled in developmental education courses.